CHARACTERISTICS AND LIFE EXPERIENCES ASSOCIATED WITH RECEIVING A RAPE DISCLOSURE WITHIN A NATIONAL TELEPHONE HOUSEHOLD PROBABILITY SAMPLE OF WOMEN. Issue 5 (July 2014) - Paul, Lisa A.; Walsh, Kate; McCauley, Jenna L.; Ruggiero, Kenneth J.; Resnick, Heidi S.; Kilpatrick, Dean G.
<x xml:space="preserve">Abstract</x> Disclosure of rape to informal support sources is relatively common, but not well understood. This study expands our limited knowledge of disclosure recipients' experience by examining associations between their sociodemographic and life experiences with receipt of a rape disclosure and encouragement of the victim to formally report her assault. Over 35% of the 3, 001 community‐residing women in this national sample reported receiving a rape disclosure. Women who had a personal history of sexual assault, met lifetime diagnostic criteria for posttraumatic stress disorder or depression, met past‐year diagnostic criteria for substance abuse, engaged in monthly binge drinking and nonexperimental substance use, and sought help for emotional concerns were significantly more likely to be recipients. Approximately two thirds (69%) of disclosure recipients encouraged the victim to formally report the rape, and encouragement was also significantly associated with these characteristics. Implications of these findings for improving the disclosure process are provided.